IMPLEMENTASI MODEL PEMBELAJARAN INKUIRI TERSTRUKTUR UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI GETARAN DAN GELOMBANG - Azizah, Wafiq Maula; Qosyim, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the improvement of students' critical thinking skills after the implementation of a structured inquiry learning model on vibration and wave materials. This study applies a quantitative approach with a one group pretest-posttest design. The subjects were 28 students in grades VIII-F SMP Muhammadiyah 2 Taman. The instruments used included pretest and posttest questions, observation sheets on learning implementation, and student response questionnaires. The preparation of test instruments refers to indicators of critical thinking skills, namely providing explanations, providing further explanations, and strategies and tactics. The results showed that students' critical thinking skills improved with an average N-gain value of 0.67 in the medium category. The normality test showed a significance value in the pretest of 0.322 and 0.077 in the posttest so that the data was declared to be normally distributed. The results of the paired t-test showed a significance value of < 0.001 which indicates a significant difference between the pretest and posttest scores. The implementation of learning at both meetings obtained a percentage of 100% with the category of very good. Meanwhile, the students' response obtained an average percentage of 90.97% with the very good category. Overall, the structured inquiry model is effective in improving students' critical thinking skills.